Reorienting Intimacies: Felix Gonzalez-Torres’s First Canadian Solo Exhibition: A Conversation with Rui Mateus Amaral - Coby, Laura M. (Performance Matters, 2023)
With widespread global lockdowns in our recent collective memory, we know what it is like to be isolated from one another and what it might mean for shared touch or breath to be forbidden. In a violent political climate, still feeling the aftershocks from the COVID-19 pandemic, how might we reassess what intimacy can look like? Attending to mass loss and grief, I turn to the work of queer, contemporary artist Felix Gonzalez-Torres to consider to how the sensorial and material coincide with individual and collective affect. Moving through essay and interview forms, this piece looks at Felix Gonzalez-Torres’s first solo exhibition in Canada, Summer/Winter, curated by Rui Mateus Amaral at the Museum of Contemporary Art in Toronto in 2022. This timely exhibition began as Summer, but as time progressed, the show transitioned into Winter, altering the composition of many of the installation artworks. In conversation with Amaral, we explore interpretive possibilities, curatorial practices, transitional tensions, significance of place, and life-affirming grief present in the show. Amaral’s curatorial choreography considers how spectators orient themselves in relation to the artworks and, in turn, how they might reorient themselves towards one another and the world outside of the museum walls. Through theoretical vignettes, in conversation queer of color theorists and performance scholars, this piece explores the generative possibilities of loss in Gonzalez-Torres’s work and how we might turn to the past to imagine more kind and pleasurable futures in the present. By engaging deeply with Gonzalez-Torres’s artwork and Amaral’s curation, this piece thinks through the affective, choreographic, political, and relational registers of Summer/Winter to envision otherwise possibilities for how to care for one another.